Impact Of Educational Units According To Bybee 5Es Model To Learn Some Basic Tennis Skills - Maryam Abdul-Sattar Jabbar (Wahid Hasyim University, 2026)
This study aimed to identify impact of educational units based on Bybee 5Es model to develop some basic tennis skills. It also aimed to demonstrate effectiveness of Bybee 5Es model to improve performance of serve, forehand, and backhand strokes in tennis among national team players. The researcher used experimental method with a two-group equivalent design control and experimental as it was suitable for nature of problem to be solved. Study community consisted of 12 players from the national tennis team representing various Iraqi clubs, while sample was selected using simple random sampling. Educational units were implemented from 1/2/2026 until 1/5/2026, at a rate of two units per week, with a duration of 90 minutes for each educational unit, included 14 educational units. The researcher concluded from results that appeared that use of educational units using Bybee 5Es model had a positive impact to learn and developing selected skills in research compared to methods used by coaches, as Bybee 5Es model contributed to enhancing understanding and applying skills accurately and correctly. The researcher recommends adopting Bybee 5Es model as an important part of tennis training for players of different ages, applying this model in different sports, whether individual or group, and for both genders.